Aplikasi Mobile Salary Report Menggunakan Firebase Berbasis Android Pada PT ISMATIUR - Rozzi Kesuma Dinata, Risawandi, Omy Hamzah (LPPM-UNIKI, 2021)
The use of the Android operating system on smartphones has increased. However, there are still many agencies, such as PT ISMATIUR, that still use the manual method in sending employee salary reports. In this study, the authors developinformation technology in mobile form, namely the employee salary report application at PT ISMATIUR which will makeit easier for admins and employees to send or receive salary reports, employees receive reports in the form ofnotifications and view the report easily and efficiently. Broadly speaking, this android application will use AndroidStudio and Firebase services. Firebase is a service from Google in developing applications. Firebase has many featuresand can be used by developers to develop an application professionally, making it easier for employees to send andreceive reports quickly, easily and safely than before, which was still using the manual method.